Vibrational analysis of paraelectric–ferroelectric transition of linbo3: An ab-initio quantum mechanical treatment - Gentile, Francesco Silvio; Diana, Rosita; Panunzi, Barbara; Caruso, Ugo; Platonenko, Alexander; Pascale, Fabien; Dovesi, Roberto (MDPI, 2021)
The phase transitions between paraelectric (PE) and ferroelectric (FE) isomorph phases of LiNbO3 have been investigated quantum mechanically by using a Gaussian-type basis set, the B3LYP hybrid functional and the CRYSTAL17 code. The structural, electronic and vibrational properties of the two phases are analyzed. The vibrational frequencies evaluated at the Γ point indicate that the paraelectric phase is unstable, with a complex saddle point with four negative eigenvalues. The energy scan of the A2u mode at −215 cm−1 (i215) shows a dumbbell potential with two symmetric minima. The isotopic substitution, performed on the Li and Nb atoms, allows interpretation of the nontrivial mechanism of the phase transition. The ferroelectric phase is more stable than the paraelectric one by 0.32 eV. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.--//-- Published under CC BY 4.0 licence.
FSG acknowledges the CINECA award under the ISCRA initiative (HP10BJO47B) for the availability of high-performance computing resources and support.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; CRYSTAL code; DFT-simulation; Ferroelectricity; IR spectrum; Isotopic substitution; Lithium niobate; Vibrational mode symmetry